Canonical Correlation Analysis of Lead Concentration in Hair Impacted With IQ, Antisocial Behavior, and Hand Strength at High School Students Community - Sri Harini; Indah Tri Susilowati; Noviana Dewi; Tri Harningsih; Endang Widhiyastuti; Purwati Purwati; Dewi Saroh; Angga Dwi Mulyanto; Muhammad Saefi (Journal of Multidisciplinary Applied Natural Science, 2025)
Lead is widely found in the environment and it is a heavy metal element that has a neurotoxic effect. Unlike other elements, lead does not provide its benefits in the human body. Neurotoxicity describes the neurophysiological changes caused by exposure to toxic agents, which can be manifested by changes in various functions of the nervous system. The aim of this research was to examine the associations between high school students' lead hair levels, intelligence quotient (IQ) scores, propensities for antisocial behavior, and hand grip strength. This research used canonical correlation analysis. Lead levels were detection by flame atomic absorption spectrometry (AAS). Antisocial behavior tendency data was measured using a 21-item antisocial tendency scale using the aspects listed in diagnostic statistical mental disorder (DSM) V which had previously been tested for validity and the reliability. The IQ level was measured using the Wechsler adult intelligence scale (WAIS) test, while the hand muscle strength test was measured using a hand grip dynamometer. Based on the results of the canonical correlation analysis, the research results showed that there was no correlation between lead levels in hair and antisocial behavior tendencies, but there was a relationship between lead levels in hair and IQ levels and hand muscle strength.